الغيرية في شعر مسكين الدارمي - الثبيتي، غزية محمد سهل (جامعة أم القرى, 2023)
يهدف البحث إلى دراسة الغيرية في شعر مسكين الدارمي من خلال استنطاق النص الشعري ورصد العلاقة بين الذات الشاعرة والغيرية التوافقية حينا والتعارضية حينا آخر، وبيان فاعلية الغيرية كمحرك دلالي للنص الشعري بشتى تمظهراته الشكلية والمضمونية. وتوصلت النتائج إلى أن الغيرية أسهمت إيجابا في الإبداع الشعري عند مسكين الدارمي الذي تميز بالتنوع والثراء، إضافة إلى ارتباطه بالبيئة والجوانب الدينية والثقافية والمجتمعية التي تواءم معها فأثراها وأثرته. The research aims to study otherness Miskin Al-Dārāmī's poetry by interrogating the poetic text and monitoring the relationship between the poet's self and the harmonious otherness at one time and the oppositional one at another, and to demonstrate the effectiveness of otherness as a semantic engine for the poetic text in its various formal and content manifestations. The results concluded that otherness contributed positively to the poetic creativity of Miskin Al-Darami, who was distinguished by diversity and richness, in addition to its association with the environment and the religious, cultural and societal aspects with which harmonized with it and contributed to its enrichment.
Keywords: الشعر العربي -- الإبداع الشعري -- الأغراض الشعرية -- البناء الفني